2018
DOI: 10.7759/cureus.2741
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency and Associated Risk Factors in the US Population (2011-2012)

Abstract: Introduction1,25-dihydroxyvitamin D3 (cholecalciferol), the hormonally active form of vitamin D3, is a lipid-soluble compound that plays a significant role in clinical medicine due to its potent effects on calcium homeostasis and bone metabolism. Since foods containing natural vitamin D are rare, the primary source of the compound remains its nonenzymatic dermal synthesis through exposure to ultraviolet rays in sunlight. Although uncommon in most developed countries, recent literature has demonstrated that sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
3
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 13 publications
3
117
3
6
Order By: Relevance
“…Information on important lifestyle risk factors as smoking, obesity, unhealthy diet and physical inactivity were not available in the current study and confounding by these factors are thereby possible. However, these factors are most often found related to lower blood levels of vitamin D. It is therefore more likely that adjustment for these factors would lead to the opposite finding in our study, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Information on important lifestyle risk factors as smoking, obesity, unhealthy diet and physical inactivity were not available in the current study and confounding by these factors are thereby possible. However, these factors are most often found related to lower blood levels of vitamin D. It is therefore more likely that adjustment for these factors would lead to the opposite finding in our study, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency in vitamin D is a global concern; approximately one billion people in the world have low vitamin D levels [3]. In the United States, according to the National Health and Nutrition Examination Survey 2011-2012, about 40% of men and women were vitamin D deficient [4]. In Saudi Arabia, approximately 81% of the different population groups has vitamin D deficiency, and this condition is more prevalent in women compared to men [5].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that only 18% of enrolled persons had VitD levels of 12‐19 ng/mL; just 4% had levels below 12 ng/mL; 37% had levels of 20‐29 ng/mL; and 38% actually had levels of 30 ng/mL or more. That means that only 22% of participants in the D2d Study were VitD deficient, while in the general US population the prevalence of this degree of VitD deficiency is nearly 40% and that in the Australian population is 31%, suggesting that the study population was one for which VitD therapy may not be expected to be effective. It is also noteworthy that the per‐protocol analysis, in which only patients who strictly followed the instructions and completed the entire trial were analyzed, showed that diabetes risk reduction was 16%.…”
Section: What Does the D2d Study Tell Us?mentioning
confidence: 98%